A pilot study to evaluate the efficacy of fibrin glue in attaching full thickness skin graft in repair of cicatricial ectropion - Vichare, Nitin V.; Singh, Jaswinder (International Surgery Journal, 2017)
Background: Traditionally, sutures are used to attach skin graft. Periocular skin reconstruction is peculiar in respect of constant movement of the graft bed due to lid movements. This study was aimed at evaluating the use of fibrin glue in skin graft for cicatricial ectropion. Methods: This was prospective, non-randomized, interventional study. Total 10 patients with cicatricial ectropion were recruited. After dissection of scar, skin defect was covered with full thickness post auricular graft. Fibrin glue used to attach the graft over host bed. Bolster tied and bandage applied. Patients were evaluated for graft stability, opposition of graft host junction and graft uptake. Results: The mean age was 30.9 years. Patients were divided into three groups i.e. 20-30 years, 30-40 years and 40-50 years. There were 05 patients (50%) in first group, 03 patients (30%) in second group and 02 patients (20%) in third group. Majority (90%) were male. Following injury 70% patients reported between 1-3 years. Grade 3 ectropion was most common (60%). Average duration of surgery was 79.3 min (standard deviation of 14.15 min). Horizontal dimensions of graft, 32 mm maximum and 26 mm minimum (average 29 mm). Vertical dimensions of graft, 18 mm maximum and 12 mm minimum (average 15 mm). Graft uptake was complete in all cases. No cases of graft infection or necrosis. However, 03 patients had residual ectropion. Conclusions: Use of fibrin glue in attaching full thickness skin graft is an effective and safe technique with good uptake and stable graft host junction.